Volunteers’ growth mindset and continuance intention: what are the roles of nostalgia and positive emotions? - Cho, Heetae; Lee, Hyun-Woo; Kim, Taehee (Frontiers in Psychology, 2023)
This study examined the cognitive and affective aspects of volunteering experiences by focusing on the relationships between volunteers' growth mindset, nostalgia, positive emotions, and their intention to continue volunteering. A total of 364 responses were collected from volunteers who had volunteered within the past five years. Results showed that the growth mindset had a positive effect on nostalgia, which in turn positively affected valenced emotions toward volunteering. Nostalgia and volunteers' positive emotions positively influenced their intention to continue volunteering. All indirect effects via nostalgia were significant. This study lays the groundwork to identify the role of nostalgia in volunteerism and contributes to extending the literature on growth mindset and mindset theory.